Kakawin Bualu Dre?tha Langö Sebuah Kajian Resepsi Sastra - Ady Andyka Putra, I Putu; Wijana, I Made; Bawa, A. A. Gede (Humanis, 2017)
The study of Kakawin Bualu Dre?tha Langö was conducted due to the deviation of the story’s context. This kakawin does not convey the story of Ramayana and Mahabrata anymore, meanwhile it is more focused in describing Dharma Çanthi covered Dre?tha Langö. Besides that, the prominently concept of Dharma Çanthi  and Dre?tha Langö could create a lot of reception of I Ketut Sarya as the writer of Dharma Çanthi  in Kakawin Bualu Dre?tha Langö. This study is aimed at analyzing both formal and narrative structures of Kakawin Bualu Dre?tha Langö, and analyzing the form of arts reception from Kakawin Bualu Dre?tha Langö. The data of this study were collected through observation method. The data were analyzed descriptively and analytically, then the data were analyzed based on the structural principle and theory because every work has its own structure. The next analysis was used arts reception as the main theory. The result of the study show the formal and narrative structure. The formal structure is related with guru-laghu, wr?ta, m?tra, ga?a, canda, composition and connection of line, abode, beat, with ala?kara. Narrative structure consist of sequences building, such as melasti, tawur kasanga, pangrupukan, nyepi, ngembak geni. Next, it is about the language used in the story, then the analysis of reception form Dharma Çanthi, such as market, exhibition, entertainment, expressing opinion (pararem), and giving the charter certificate.